Water Quality Identification and Analysis of Saguling Reservoir, West Bandung Regency - Dhoni Maranata; Runi Asmaranto; Sri Sudaryanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The Saguling Reservoir in West Bandung Regency is crucial for local water supply and biodiversity. However, water quality has significantly declined due to human activities, environmental changes, and poor waste management. This degradation jeopardizes the reservoir's clean water supply and the ecological health of surrounding communities. This research used the STORET (Storage and Retrieval) method to assess water quality through purposive sampling in the most affected zones, analyzing physical, chemical, and biological parameters at multiple depths. Key indicators, such as dissolved oxygen, nutrient concentrations, and heavy metal presence, were measured. Results show severe water quality deterioration, especially in deeper sections with less sunlight and aeration. Elevated nitrate and phosphate levels, mainly from agricultural runoff and residential waste, exceeded environmental safety standards. Toxic heavy metals like lead and mercury were also detected, posing serious risks to aquatic life and human health. The study highlights that deeper water zones are critically impacted by pollutants, stressing the need for better regulatory frameworks and waste management. Immediate strategic interventions are crucial to restore and protect the Saguling Reservoir's water quality for future generations.